Les apprentissages développés au cours de transitions professionnelles : le cas des responsables adjointes de crèches collectives - Michèle Lemeunier-Lespagnol; Richard Wittorski (Recherches en Éducation)
As part of a "transition" between two professional positions, we will try to define how early childhood employees, pediatric nurses and early childhood educators experience the professional transition to the role of day-nursery deputy manager. We will also analyze the professional development process involved and how identities are formed based on the employees we met with; we would like to understand whether this transition to the role of deputy head represents continuity or a break in their professional career. We also studied certain elements of how employees’ experience taken into account as part of this professional transition.